Flood Risk Assessment and Mitigation Strategies for the Sinjai and Tangka River Catchments in Indonesia using Hydraulic Modeling and Spatial Analysis - Karamma, Riswal; Badaruddin, Sugiarto; Mustamin, Muhammad Rifaldi; Mukrim, Muhammad Ihsan (Engineering, Technology & Applied Science Research, 2025)
This study aims to address the persistent flooding in Sinjai District, Indonesia, by developing a comprehensive spatial flood risk model. The development of this model was conducted using hazard, vulnerability, and capacity index data. The research first determines the weighted scores of the hazard, vulnerability, and capacity indices to categorize areas into high, medium, and low flood risk zones as a reference in developing flood mitigation. The study further uses the Unmanned Aerial Vehicle (UAV) technology to facilitate the collection of topographic data, which are then used as an input in the hydrological and hydraulic analysis. The overarching objective of this research is to provide insights and recommendations to policymakers, with the aim of informing effective strategies for reducing the flood risk. The results indicate that low-risk areas encompass 564.45 hectares, medium-risk areas extend to 645.83 hectares, and high-risk areas cover 46.19 hectares. The proposed flood control measures include the construction of retention ponds, embankments, and river normalization. These interventions have the potential to reduce up to 507.12 hectares, equivalent to 40.36% of the inundation area, thereby reducing the impact of flooding. The findings provide important guidance for policymakers in making decisions, devising mitigation strategies, and promoting sustainable development in the region.